EFEKTIVITAS PROGRAM DINAS KEBUDAYAAN DAN PARIWISATA PADA PESTA BUDAYA TABUIK DI KOTA PARIAMAN PROVINSI SUMATERA BARAT - Octarina "; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Based on the Law of the Republic of Indonesia No. 10 Year 2009 on Tourism inchapter 1 verse 10 says : " strategic areas of tourism is the area that has the primary functionof tourism or have the potential for development of tourism which has a significant impact onone or more aspects , such as economic growth , social and cultural , environmental support ,and defense and security . " the legal basis is the reason for the Department of Culture andTourism cultural Festival Tabuik Pariaman enter the work program which is used as aplatform to attract tourists to come to the city of Pariaman .The purpose of this study was to determine whether the program created by theDepartment of Culture and Tourism of Pariaman already running equally effective as theprevious objectives and determine the impact of the program for the City pariaman . Thisresearch was conducted at the Department of Culture and Tourism of Pariaman , usingqualitative descriptive method with data collection through interviews , observation anddocumentation of the people who play an important role in the Program of Culture andTourism in Tabuik Cultural Festival in Pariaman City West Sumatra province . This researchwas conducted by using the theory of Richard M. Steers (1985 ) about the factors thatinfluence the effectiveness of an organization .The results of this study indicate that the Program of Culture and Tourism CulturalFestival Tabuik in Pariaman City West Sumatra province has been effective . It can be seenfrom the increasing number of tourists both foreign and domestic tourists/ Kota Pariamanespecially on Tabuik Cultural Festival . Increasing the number of visitors also have animpact on improving the economy of communities around the city of Pariaman and turn oncoastal tourism and marine tourism in Pariaman City .Keywords : Effectiveness , Program , and Tourism